Serious Daring : The Fiction and Photography of Eudora Welty and Rosamond Purcell - Cole, Susan Letzler, 1940- (Book collections on Project MUSE., 2016)
Serious Daring is the story of the complementary journeys of two American women artists, celebrated fiction writer Eudora Welty and internationally acclaimed photographer Rosamond Purcell, each of whom initially practiced, but then turned from, the art form ultimately pursued by the other. For both Welty and Purcell, the art realized is full of the art seemingly abandoned. Welty's short stories and novels use images of photographs, photographers, and photography. Purcell photographed books, texts, and writing. Both women make compelling art out of the seeming tension between literary and visual cultures. Purcell wrote a memoir in which photographs became endnotes. Welty re-emerged as a photographer through the publication of four volumes of what she called her "snapshots," magnificent black-and-white photographs of small-town Mississippi and New York City life. Serious Daring is a fascinating look at how the road not taken can stubbornly accompany the chosen path, how what is seemingly left behind can become a haunting and vital presence in life and art